Cognitive Behavioral Therapy for Diabetic Patients - Mendrofa, Trisman Basri; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Ginting, Chrismis Novalinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Improving self-care in T2DM patients is critical so that patients can achieve targeted blood glucose levels to prevent complications and independently perform daily tasks to improve their quality of life and life satisfaction. Psychological intervention is believed to be able to change a person's behavior towards a better direction in disease control and prevention. This study measures the impact of Cognitive-Behavioural Therapy (CBT) interventions on the self-care management of T2DM patients. This quasi-experimental study used a pretest-posttest with a control group design. The research subjects were divided into two groups, namely the intervention group (35 people) and the control group (35 people). The study was conducted at the Tello Primary Health Center in April 2021. The data were analyzed using the t-dependent test (?=0.05). The results of the study showed that in the intervention group, there were differences in the self-care management of T2DM patients before and after being given CBT, which included eating patterns (p less than 0.001; 95%CI -6.663-(-4.796)), physical activity (p less than 0.001; 95% CI -5.344-(-4.370)), and attitude (p= less than 0.001; 95%CI -13.086-(-10.114)). In the control group, there was no difference in the self-care management of T2DM patients, which included eating patterns (p= 0.083; 95%CI -0.183-0.012), physical activity (p= 0.058; 95%CI -0.291-0.005), and T2DM patients attitudes (p= 0.094; 95%CI -0.225-0.003). This means that CBT effectively improves the self-care management of T2DM patients.Abstrak: Peningkatan perawatan diri pada pasien DM tipe 2 sangat penting dilakukan agar pasien dapat mencapai kadar glukosa darah yang ditargetkan untuk mencegah komplikasi dan secara mandiri melakukan tugas sehari-hari sehingga meningkatkan kualitas hidup dan kepuasan hidup mereka. Intervensi psikologis dipercaya mampu mengubah perilaku seseorang ke arah yang lebih baik dalam pengendalian dan pencegahan penyakit. Studi ini bertujuan mengukur dampak intervensi Cognitive–behavioural therapy (CBT) terhadap manajemen perawatan diri pasien DM tipe 2. Quasi-experimental study ini menggunakan desain pretest-posttest with control group design. Subjek penelitian dibagi ke dalam dua kelompok yaitu kelompok intervensi (35 orang) dan kelompok kontrol (35 orang). Penelitian dilakukan di Puskesmas Tello pada bulan April tahun 2021. Data dianalisis menggunakan uji t-dependent (p=0,05). Hasil studi menunjukkan bahwa pada kelompok intervensi terdapat perbedaan manajemen perawatan diri pasien DM tipe 2 sebelum dan sesudah diberikan CBT yang meliputi pola makan (p kurang dari 0,001; 95%CI -6,663-(-4,796)), aktivitas fisik (p kurang dari 0,001;95%CI -5,344-(-4,370)), dan sikap (p kurang dari 0,001; 95%CI -13,086-(-10,114)). Sedangkan pada kelompok kontrol, tidak terdapat perbedaan manajemen perawatan diri pasien DM tipe 2 yang meliputi pola makan (p= 0,083; 95%CI -0,183-0,012), aktivitas fisik (p= 0,058;95%CI -0,291-0,005), dan sikap pasien DM (p= 0,094; 95%CI -0,225-0,003). Artinya CBT efektif dalam meningkatkan manajemen perawatan diri pasien DM tipe 2.